2013
DOI: 10.3109/13880209.2013.764328
|View full text |Cite
|
Sign up to set email alerts
|

The effects of qindan-capsule-containing serum on the TGF-β1/ERK signaling pathway, matrix metalloproteinase synthesis and cell function in adventitial fibroblasts

Abstract: (2013) The effects of qindan-capsule-containing serum on the TGF-β1/ERK signaling pathway, matrix metalloproteinase synthesis and cell function in adventitial fibroblasts, Pharmaceutical Biology, 51:6, 712-721, DOI: 10.3109/13880209.2013 Context: Qindan capsule (QC), a compound used in traditional Chinese medicine, has been used as an anti-hypertensive agent in clinical settings for years. Our previous studies have shown that QC can improve the morphological index of the artery, down-regulate the collagen vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…These results all indicate that ACY1 functions via the ERK pathway. Furthermore, activation of ERK increases the expression of TGF-β, another important factor involved in tumor progress (13,(15)(16)(17), and TGF-β could therefore directly attenuate the immune system and promote tumor proliferation (13,17). Thus, decreased expression of TGF-β could lead to tumor inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results all indicate that ACY1 functions via the ERK pathway. Furthermore, activation of ERK increases the expression of TGF-β, another important factor involved in tumor progress (13,(15)(16)(17), and TGF-β could therefore directly attenuate the immune system and promote tumor proliferation (13,17). Thus, decreased expression of TGF-β could lead to tumor inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, this revealed that silencing of ACY1 reduced the level of ERK1 expression in colorectal cancer tissue, which indicates that there is an overexpression of ERK1 along with ACY1 in colorectal cancer. In addition, since it is well known that activation of ERK leads to increased TGF-β1 expression (13,15,16), the association between ACY1 and TGF-β1 expression was measured, which revealed a positive association between the two. The results of the present study indicate that the ERK and TGF-β1 function downstream of ACY1 and facilitate the tumor-promoting effect of ACY1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive or inappropriate expression of MMP expression may contribute to the pathogenesis of tissue-destructive processes in a wide variety of diseases, including pulmonary hypertension [11]. Matrix metalloproteinase-2 (MMP-2) is expressed ubiquitously in various cell types including cardiomyocytes, endothelial cells, fibroblasts, and vascular smooth muscle cells and plays a crucial role in angiogenesis regulation [12][13][14]. MMP-2 and -9 are important players in several cardiovascular diseases including atherosclerosis, ischemic heart disease, and heart failure [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a highly prevalent disorder and a major risk factor for cardiovascular diseases (2). Vascular remodeling (VR) occurs during normal angiogenesis and under various pathological situations, including hypertension (3). VR is an active process of structural alteration that involves changes in at least four cellular processes -cell growth, cell death, cell migration, and the production or degrada tion of the extracellular matrix -and is the common pathological basis of a variety of cardiovascular diseases (4).…”
Section: Introductionmentioning
confidence: 99%